HUBUNGAN SHIFT KERJA DAN DURASI MENGEMUDI DENGAN KELELAHAN KERJA PADA PENGEMUDI BUS RAPID TRANSIT KORIDOR I KOTA SEMARANG - Siti Nur Jayanti; Baju Widjasena; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Fatigue was body protection mechanism to avoid further damage so recovery Fatigue was a body protection mechanism that can prevent any further damage because of recovery after a break. Drivers expected to run dynamic and complex job with repetitive tasks and needed ongoing attention. These job was extremely tiring. The purpose of this study was to analyze the factors of shift work and duration of driving associated with fatigue in the Bus Rapid Transit Drivers Coridor I Terminal Mangkang – Terminal Penggaron. The independent variable in this study was fatigue. While the dependent variable were work shift and duration of driving.. This study was observational analytic with cross sectional study approach. The research instrument were questionnaires, observation sheets and Deary Liewald Reaction Time. This study took a sample of 40 drivers using the total sampling method. The measurement results showed that drivers had mild and moderate fatigue. Chi-square statistical test results showed that there were no relationship between work shift (p = 0,747) and duration of driving (p = 0,519) with fatigue. It is recommended that BLU Trans Semarang should provide rest place for the drivers and stand-by drivers at Terminal Mangkang. It's suggested that the BRT drivers should maintain a healthy lifestyle by reducing smoking and stretching the legs, arms, shoulders and the entire body to release muscle tension when getting some rest.